2010
DOI: 10.1007/s10652-010-9166-z
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase SPH modelling of advective diffusion processes

Abstract: This paper deals with a two-dimensional numerical model based on the smoothed particle hydrodynamics (SPH) technique for the evaluation of the concentration field of pollutants in water. A SPH model is formulated to solve the fickian diffusion equation applied to pollutants with the same density as the water. A lagrangian SPH formalism of the advective diffusion equation is also developed for pollutant-water, taking into account the effects of molecular diffusion and natural advection induced by differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…It can be found that the moving speed of the leading edge of Figure 3c owing to the effects of advection and diffusion is larger than the one of Figure 3a resulting from the effect of pure advection. Furthermore, the simulated results show good agreement against the exact solutions obtained in [33]. It can be concluded that the present model is capable of solving steep gradient or discontinuous solutions in concentration fields of advection-dominated, advection-diffusion, and diffusion-dominated problems.…”
Section: A Unit-step Tracer In a 1d Uniform Flowsupporting
confidence: 65%
See 2 more Smart Citations
“…It can be found that the moving speed of the leading edge of Figure 3c owing to the effects of advection and diffusion is larger than the one of Figure 3a resulting from the effect of pure advection. Furthermore, the simulated results show good agreement against the exact solutions obtained in [33]. It can be concluded that the present model is capable of solving steep gradient or discontinuous solutions in concentration fields of advection-dominated, advection-diffusion, and diffusion-dominated problems.…”
Section: A Unit-step Tracer In a 1d Uniform Flowsupporting
confidence: 65%
“…Equation (28) can be obtained with different derivations [29,31,33]. It is also suitable for the situations that the diffusion processes is anisotropic or inhomogeneous, and in such situations, the coefficient D u will be a tensor and has the elements of D uxx , D uxy , D uyx , and D uyy [30].…”
Section: Approximated Advection-diffusion Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, different SPH models have been widely studied and applied in the field of fluid mechanics. Recently, SPH methods have been widely applied in single-phase flows [12][13][14][15], multiphase flows [16][17][18], and diffusion processes between different density flows [19,20]. Compared to the Euler method, the existing Lagrangian SPH method has performed well in simulating the motion characteristic of particles.…”
Section: Smooth Particle Hydrodynamics Methodsmentioning
confidence: 99%
“…Since then, it has been used in several research areas, e.g. coastal engineering [3][4][5][6][7], flooding forecast [8][9][10][11], solid body transport [12][13][14][15], soil mechanics [16][17][18][19][20], sediment erosion or entrainment processes [21][22][23][24], fastmoving non-Newtonian flows [25][26][27][28][29][30][31][32][33], flows in porous media [34][35][36], solute transport [37][38][39], turbulent flows [40][41][42] and multiphase flows [43][44][45][46][47], not to mention manifold industrial applications (see, for instance [48][49][50]…”
Section: Introductionmentioning
confidence: 99%